Design and virtual implementation of a biomedical registry framework for the enhancement of clinical trials: colorectal cancer example - Athanasios Kotoulas; George Lambrou; Dimitrios-Dionysios Koutsouris (BMJ Health & Care Informatics)
Introduction Clinical trials generate a large volume of literature and a vast amount of data. Following the 'open science' model, data sharing has enormous potential to strengthen scientific research. Currently, to the best of our knowledge, there is no existing web based Hellenic biomedical registry that displays available patients for clinical trials, providing direct access to registered physicians to all data, assisting them in finding eligible patients in the initial clinical trial recruitment process.Methods This paper describes the design and virtual implementation of a web based prototype biomedical registry in Greece. The system represents an eGovernment framework proposal for the central storage of patients' biomedical information and the operations associated with this process. The increasing tendency to include molecular data as prerequisite elements in clinical trials is adopted in the registry philosophy. The designed system is based on free, open source software and it is implemented virtually on a local host environment.Results Using colorectal cancer as an example, valid data from patients increases the reliability index, demonstrating the functionality of the web application.Conclusion In conclusion, the combination of biomedical data and information technology in order to display potential participants per health unit, facilitates recruitment for clinical trials.